Psychometric Properties of the Millon Clinical Multiaxial Inventory–III in an Arabic Clinical Sample Compared With American, Italian, and Dutch Cultures - Alareqe, Naser Abdulhafeeth; Roslan, Samsilah; Nordin, Mohamad Sahari; Ahmad, Nor Aniza; Taresh, Sahar Mohammed (Frontiers in Psychology, 2021)
ABSTRACT Millon Clinical Multiaxial Inventory MCMI–III (Millon, Millon, Davis, & Grossman, 2006) is a multidimensional measure of psychopathology with excellent construct validity, test-retest reliability as well as internal consistency. Factor analysis of the MCMI-III has produced mixed results, extracting parsimonious three-factor solutions, or replicating the original four-factor solution in psychiatric samples from Western countries. However, little work has been done on the psychometric properties of the MCMI–III using non-Western psychiatric samples. Outpatients (N=212) completed the MCMI–III during a Semi-Structured Interview. Eight Exploratory Factor Analysis (EFA) methods were used to explore the underlying structure of MCMI–III. Skewness, kurtosis, and descriptive statistics confirmed that MCMI–III’s scales were normally distributed. High internal consistency was found. The eight EFA methods applied to the 24 clinical scales identified a consensual three-factor solution: factor I (Internalizing Psychopathology; 18 scales), factor II (Externalizing Psychopathology; 4 scales) and factor III (Psychological Disturbance; 2 scales), accounting for a total of 72 % of the common variance. Regarding the cross-cultural equivalence of the MCMI–III structure, Tucker’s congruence coefficient (Φ) was used and confirmed that internalizing (F1) and externalizing psychopathology (F2) factors obtained in this study are similar to high versus low psychopathology and emotional constraint factors provided by the Haddy, Strack, & Choca (2005)’s American study (Φ was 0.86 and 0.97). These two factors are also similar to the general adjustment and antisocial acting out factors provided by the Craig & Bivens (1998)’s American study (Φ was .82 and .96). The first two factors in this study also reflect high similarity with the factor solutions obtained with the MCMI-III’s Italian and Dutch versions (Pignolo et al., 2017; Rossi, van der Ark, & Sloore, 2007). Despite using a psychiatric sample from a non-Western culture, the two factors identified for this MCMI–III Arabic version were similar to those reported on studies with MCMI–III using primarily Western samples (Craig & Bivens, 1998; Rossi et al., 2007).